Elimination of hepatitis C in a hospital characterized by infectious diseases - Han, Ying; Zheng, Mei; Meng, Huan; Han, Jinyu; Chen, Jin; Wang, Yajie (Frontiers in Public Health, 2023)
Background The World Health Organization has proposed to eliminate hepatitis C by 2030, yet there is still a large gap to the goal. Screening for hepatitis C is cost-effective and efficient in medical institutions. The aim of this study was to identify the key populations for HCV antibody screening in hospital characterized by infectious diseases, and provide estimates of the proportion of HCV-infected persons in the Beijing Ditan hospital completing each step along a proposed HCV treatment cascade. Methods A total of 105,112 patients who underwent HCV antibody testing in Beijing Ditan hospital between 2017 and 2020 were included in this study. HCV antibody and HCV RNA positivity rate were calculated and compared by chi-square test. Results The positivity rate of HCV antibody was 6.78%. The HCV antibody positivity rate and the proportion of positive patients showed an upward trend along with age in the five groups between 10–59 years. In the contrary, a decreasing trend was observed in the three groups above 60 years. Patients with positive HCV antibody were mainly from the Liver Disease Center (36.53%), the Department of Integrative Medicine (16.10%), the Department of Infectious Diseases (15.93%) and the Department of Obstetrics and Gynecology (9.44%). Among HCV antibody positive patients, 6,129 (85.95%) underwent further HCV RNA testing, of whom 2097 were HCV RNA positive, the positivity rate was 34.21%. Of the patients who were HCV RNA positive, 64.33% did not continue with HCV RNA testing. The cure rate for HCV antibody positive patients was 64.98%. Besides, there was a significant positive correlation between HCV RNA positivity rate and HCV antibody level (r = 0.992, P < 0.001). The detection rate of HCV antibody among inpatients showed an upward trend (Z = 5.567, P < 0.001), while the positivity rate showed a downward trend (Z = 2.2926, P = 0.0219). Conclusions We found that even in hospitals characterized by infectious diseases, a large proportion of patients did not complete each step along a proposed HCV treatment cascade. Besides, we identified key populations for HCV antibody screening, namely: (1) patients over 40 years of age, especially those aged 50–59 years; (2) the Department of Infectious Diseases and the Department of Obstetrics and Gynecology patients. In addition, HCV RNA testing was highly recommended for patients with HCV antibody levels above 8 S/CO.